Case report: Enfortumab vedotin induced refractory DKA and multi organ failure – a rare fatal adverse event - Kapoor, Astha Koolwal; Ellis, Carleton S.; Pandey, Deepali; Allison, Derek B.; Myint, Zin W. (Frontiers in Oncology, 2024)
There are very few therapeutic options to treat patients with locally advanced or metastatic UCUrothelial Cancer (UC). Enfortumab vedotin (EV) was recently approved by the FDA and has become a new therapeutic option for patients previously managed with conventional treatments. Despite its efficacy, EV carries the potential for infrequent yet severe adverse effects.In this report, we present a case of a patient undergoing EV treatment for urothelial carcinoma who developed refractory DKA diabetic ketoacidosis (DKA) unresponsive to escalating insulin doses and necessitating continuous renal replacement therapy. While DKA was resolved, the patient eventually succumbed to progressive maculopapular skin rash, liver failure, and respiratory failure. Additionally, the study delves into a review of cases of EV-induced refractory DKA in the literature, shedding light on the similarities in patient profiles, timelines of adverse effects and the treatment strategies employed to manage the ensuing complications.